A simplified method for studying cyclic creep behaviors of deep-sea manned submersible viewport windows. (15th December 2021) - Li, J.X.; Liu, P.F.; Tong, X.Y.
Abstract: This paper predicts the cyclic creep behaviors of deep-sea manned submersible PMMA viewport windows that experience the cyclic dive, operation and rise stages. The three-element spring-dashpot viscoelasticity/damage model is used to predict the viscoelastic behaviors of PMMA viewport windows at 1–7 km water depths during the dive stage, the creep behaviors during the operation stage, and the creep recovery behaviors during the rise stage. This model has been validated by creep experiments of PMMA materials and viewport windows under 30 MPa stress levels. The fatigue damage behaviors due to variable hydraulic pressure during the dive and rise stages are equivalently represented by the cyclic creep damage behaviors under each approximate constant pressure, which is obtained by dividing these two stages into finite pressure increments. By considering a series of factors including the dive velocity, time, depth and sequence, the cyclic creep behaviors and lifetime of the conical and spherical viewport windows at 1–7 km water depths are explored using finite element analysis. The developed method and numerical algorithm are validated by using the pressure loading-pressure holding (89.5 MPa)-pressure unloading experiments of the PMMA conical viewport window. Results show: 1. for the same dive depth and sequence, the maximum strain during the creep stage, the residual strain and damage at the end of rise stage for the conical viewport window are about twice that for the spherical viewport window with the same thickness and cone angle, and the predicted cyclic creep lifetime for the spherical viewport window is about twice that for the conical viewport window. 2. the fatigue damage is validated to be comparable to the creep damage for two kinds of viewport windows, which produces large effects on the lifetime and load-bearing ability of structures. 3. the cyclic pressure diving to different water depths aggravates the creep and damage behaviors of shells, but the pressure loading sequence corresponding to different intermediate depths (for example, 1 km-3km–5km and 3 km-5km–1km) hardly affects the cyclic creep behaviors of viewport windows. Highlights: The creep/fatigue issues for PMMA manned submersible viewport windows are studied. Fatigue damage during the dive and rise stages are replaced by the creep damage. Three-element spring-dashpot viscoelasticity/damage model is developed for creep analysis. Cyclic creep behaviors and lifetime of windows are predicted by FEA. Effects of the dive velocity, time, depth and sequence are explored.